Dedication to Beatrice Spiliadis. (Athene, : Pinacotheque, 1987)
Akrithakis, Alexis ; Alithinos, Dimitri ; Aperghis, Achille ; Aperghis Irini ; Varotsos, Costas ; Voyatzoglou, Maria ; Gazetopoulou, Yioulia ; Golanda, Nella ; Danil ; Diohandi ; Zaharioudakis, Manolis ; Zouni, Opi ; Theodoros ; Kanaghini, Niki ; Kessissoglou, Anna ; Kyriaki, Vasso ; Logothetis, Stathis ; Lycoudi, Lee ; Bouteas, Yannis ; Nicolaidis, George ; Davou, Bia ; Xagoraris, Pandelis ; Skourtis, Angelos ; Skylakos, Vassilis ; Stassinopoulos, Aspa ; Haros, Manolis ; Psychopedis, Yannis
Dedication to Beatrice Spiliadis, D. Pierides Pinacotheque, Athene, January 1987
boek